2021
DOI: 10.1016/j.psj.2020.12.039
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a dietary direct-fed microbial and Ferulago angulata extract on growth performance, intestinal microflora, and immune function of broiler chickens infected with Campylobacter jejuni

Abstract: Colonization of the gastrointestinal tract by potentially pathogenic bacteria and their shedding in animal feces is a fundamental factor for both animal health and human food safety. This study was conducted to evaluate the efficacy of salinomycin ( Sal ), direct-fed microbial ( DFM ), and Ferulago angulata hydroalcoholic extract ( FAE ) against Campylobacter jejuni in broiler chickens in a 6-week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…Other studies have shown an absence of effect of the presence of Campylobacter on the abundance of phyla (Alrubaye et al, 2019;. On a more consistent basis, studies have shown a decrease in the abundance of lactic acid-producing bacteria such as Bifidobacterium, Enterococcus and Lactobacillus when Campylobacter was present Hertogs et al, 2021;Nooreh et al, 2021;Richards et al, 2019;Sofka et al, 2015). The presence of Campylobacter also induced changes in the abundance of short-chain fatty acid-producing bacteria (SCFA), but inconsistently across studies Han et al, 2017;Hertogs et al, 2021;Saint-Cyr et al, 2017;Sakaridis et al, 2018;Taha-Abdelaziz et al, 2018;Thibodeau et al, 2015Thibodeau et al, , 2017.…”
Section: Methodsmentioning
confidence: 92%
See 3 more Smart Citations
“…Other studies have shown an absence of effect of the presence of Campylobacter on the abundance of phyla (Alrubaye et al, 2019;. On a more consistent basis, studies have shown a decrease in the abundance of lactic acid-producing bacteria such as Bifidobacterium, Enterococcus and Lactobacillus when Campylobacter was present Hertogs et al, 2021;Nooreh et al, 2021;Richards et al, 2019;Sofka et al, 2015). The presence of Campylobacter also induced changes in the abundance of short-chain fatty acid-producing bacteria (SCFA), but inconsistently across studies Han et al, 2017;Hertogs et al, 2021;Saint-Cyr et al, 2017;Sakaridis et al, 2018;Taha-Abdelaziz et al, 2018;Thibodeau et al, 2015Thibodeau et al, , 2017.…”
Section: Methodsmentioning
confidence: 92%
“…In addition to improving animal performance, these plants reduced Campylobacter colonization in the caecum of broiler chickens (Kelly et al, 2017;Nooreh et al, 2021). Surprisingly in these two studies, the decrease in the abundance of Campylobacter was associated with a decrease in the abundance of Lactobacillus in cecum (Kelly et al, 2017;Nooreh et al, 2021). During the administration of Carvacrol, the abundance of Proteobacteria increased at the expense of the abundance of Firmicutes (Kelly et al, 2017) (Table C32).…”
Section: Fibresmentioning
confidence: 92%
See 2 more Smart Citations
“…There is great interest in animal nutrition in the study of additives aimed at improving the animal health and performance. Among the additives defined as nutraceuticals, plant extracts and their essential oils can represent a valid alternative to synthetic additives (Shim et al 2010;Apajalahti and Vienola 2016;Xue et al 2020;Nooreh et al 2021). One of these nutraceuticals is ajwain (Trachyspermum copticum L.) (Mahboubi and Kazempour 2011;Mabood et al 2017).…”
Section: Introductionmentioning
confidence: 99%